Implementasi Aplikasi RememberMe sebagai Media Pengingat Tugas Berbasis Digital - Arham Arham; M. Afif Sahwan; Salma Salma; Sukma Riski Ananda (Progressive Information, Security, Computer, and Embedded System, 2025)
This study aims to develop a digital reminder application that helps users manage their daily schedules and activities more efficiently. The application is designed using the waterfall method, which includes the stages of analysis, design, implementation, testing, and maintenance. Testing was conducted using the black box method to ensure that all functions operate according to user needs. The results show that the application works well, delivers timely notifications, and can be used practically to support time management.